2019
DOI: 10.1155/2019/9327386
|View full text |Cite
|
Sign up to set email alerts
|

Yunnan Baiyao Conditioned Medium Promotes the Odonto/Osteogenic Capacity of Stem Cells from Apical Papilla via Nuclear Factor Kappa B Signaling Pathway

Abstract: Yunnan Baiyao is a traditional Chinese herbal remedy that has long been used for its characteristics of wound healing, bone regeneration, and anti-inflammation. However, the effects of Yunnan Baiyao on the odonto/osteogenic differentiation of stem cells from apical papilla (SCAPs) and the potential mechanisms remain unclear. The aim of this study was to investigate the odonto/osteogenic differentiation effects of Yunnan Baiyao on SCAPs and the underlying mechanisms involved. SCAPs were isolated and cocultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Several studies have demonstrated that MSCs increase the production of ALP only in the presence of osteogenic stimuli [24,27,32]. In agreement with these studies, our results showed a huge production of ALP, only in the presence of an osteogenic medium.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Several studies have demonstrated that MSCs increase the production of ALP only in the presence of osteogenic stimuli [24,27,32]. In agreement with these studies, our results showed a huge production of ALP, only in the presence of an osteogenic medium.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study investigates the odonto/osteogenic induction capacity of YB on stem cells from apical papilla [32,33]. Pang and colleagues reported that YB powder is rich in calcium ions, and it is the main reason for its well-known hemostatic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Deng et al[ 98 ] reported that platelet derived growth factor BB promoted SCAPs osteogenic differentiation and enhanced bone formation in calvarial defects combined with a thermosensitive hydrogel[ 98 ]. Both conditioned culture medium containing traditional Chinese herbal remedy, Yunnan Baiyao, and high glucose α-Minimal Essential Medium can promote the odonto/osteogenic differentiation of SCAPs through the nuclear factor κB signaling pathway[ 99 , 100 ]. Depletion of lysine-specific demethylase 2A enhanced the adipogenic and chondrogenic differentiation potentials of SCAPs[ 101 ].…”
Section: Diverse Differentiation Of Dmscsmentioning
confidence: 99%
“…In fact, the anti-HIV activity of the aklaine extract of bamoo leaf declined by removal of the lignin–carbohydrate complex [ 3 ]. Although many papers have reported the utilization of alkaline extract for the treatment of oral disease, mechanistic analysis of biological actions such as bone regeneration and anti-inflammation [ 4 ], periodontal inflammation and alveolar bone loss [ 5 ], anti-oral bacterial activity [ 6 ], and alleviation of oral lichenoid dysplasia [ 7 ] by alkaline extract has been limited.…”
Section: Introductionmentioning
confidence: 99%